THE EFFECT OF VARIATION OF TEMPERATURE ON PULL TEST OF FIBERGLASS FIBER COMPOSITE MATERIALS WITH VACUUM ASSISTED RESIN INFUSION (VARI) - Dialis Okta Saputa; Ferry Setiawan; Dhimas Wicaksono (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2023)
To determine the effect of temperature variations on mixing fiberglass composite resin materials with the vacuum infusion method in the Tensile test. To determine the effect of the lowest and best temperature variations on mixing fiberglass composite resin materials with the vacuum infusion method on fotomikro. Variation fixed resin; polyester, fiber; fiberglass, vacuum; vacuum Infusion. Variable temperature of mixing resin 30˚C, 40˚C, and 50˚C. In this study, the vacuum infusion method was used, where the researcher made a specimen using the Vacuum Assisted Resin Infusion (VARI) process. In the VARI process, dry fiber is placed between the fixmold and the plastic bag, then the resin is injected after the space inside the plastic bag is under low pressure and the process continues until all parts of the fiber are wetted by the resin. After the specimen is made, then a tensile test is carried out to determine the mechanical strength of the specimen being tested. Then analyze the tensile test data using the equations used and displayed in the form of graphs and tables. This study was used to determine the effect of fiberglass composites with the vacuum infusion method on the tensile strength test. results of Tensile testing of fiberglass fiber composites and temperature variations of 30°C, 40°C, and 50°C. From the table it can be seen that the specimen with the best performance is found in the specimen with a temperature variation of 50°C, where the load that can be withheld reaches 508.56 kgf. So for maximum tensile strength it produces 11.07 MPa. Then on the specimen with a temperature variation of 40°C the best performance is 361.95 kgf. So for maximum tensile strength it produces 8.46 MPa. In specimens with a temperature variation of 30°C the best performance is 251.10 kgf. So for a maximum tensile strength of 5.67 Mpa. The average yield strength shows the results of the Tensile test of each variation, totaling 9 specimens. For the highest yield strength, a value of 9.67 MPa was obtained at a temperature variation of 50°C and for the lowest yield strength, a value of 4.13 MPa was obtained at a temperature variation of 30°C. Tensile test specimens have results where the highest yield strength or yield strength is obtained by specimens with a temperature variation of 50°C and as the stress increases, the yield strength value increases, and for the tensile strength of the material or tensile strength which has the highest value in the test, the specimens with 50°C temperature variation. Thus, the effect of temperature treatment is significant on the increase in tensile strength, but if the temperature is 30°C it will decrease the tensile strength, as at 30°C it produces an average tensile strength of 4.62 MPa. The results of the microphoto test show that at a temperature variation of 50°C there are a few voids while the 30°C variation has too many voids. Micro photo testing aims to determine the content in the composite.